2021
DOI: 10.1007/s00425-021-03755-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the polyamine biosynthesis pathway in duckweed Spirodela polyrhiza L.: presence of the arginine decarboxylase pathway, absence of the ornithine decarboxylase pathway, and response to abiotic stresses

Abstract: Main conclusion Identification of the polyamine biosynthetic pathway genes in duckweed S. polyrhiza reveals presence of prokaryotic as well as land plant-type ADC pathway but absence of ODC encoding genes. Their differential gene expression and transcript abundance is shown modulated by exogenous methyl jasmonate, salinity, and acidic pH. Abstract Genetic components encoding for polyamine (PA) biosynthetic pathway are known in several land plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
(114 reference statements)
1
6
0
Order By: Relevance
“…Similar to other plant cells, the ability of pollen to withstand stressful conditions is related to its intrinsic biochemical, physiological, and cytological characteristics, for example the production of HSPs or osmoprotectants [97], as well as the fine-tuning of ROS and Ca 2+ levels and the ability to build a cell wall suitable for new conditions [98]. PAs have often been associated with the environmental stress response as they interface with various intracellular signaling processes [11,99], such as phosphorylation [100] and cation transport [8].…”
Section: Can Polyamines Ameliorate the Damaging Effect Of Stress?mentioning
confidence: 99%
“…Similar to other plant cells, the ability of pollen to withstand stressful conditions is related to its intrinsic biochemical, physiological, and cytological characteristics, for example the production of HSPs or osmoprotectants [97], as well as the fine-tuning of ROS and Ca 2+ levels and the ability to build a cell wall suitable for new conditions [98]. PAs have often been associated with the environmental stress response as they interface with various intracellular signaling processes [11,99], such as phosphorylation [100] and cation transport [8].…”
Section: Can Polyamines Ameliorate the Damaging Effect Of Stress?mentioning
confidence: 99%
“…The other involved Put biosynthesis genes through the ADC pathway; AIH and CPA / NLP1 have not been identified in too many species. In the current study, five TaAIH and two TaNPL1 were revealed by analysis, while a single AIH and NPL1 were found in S. polyrhiza [ 30 ] and Citrus as in A. thaliana [ 31 ]. Rice showed to have one AIH and four NLP1 [ 25 ].…”
Section: Discussionmentioning
confidence: 95%
“…The occurrence of different routes for Put biosynthesis through both ADC and ODC was formerly described in different species, particularly under stressors [ 10 , 24 , 29 ]. Although ODC is absent from some species like A. thaliana and Spirodela polyrhiza [ 30 , 31 ], it was identified in Oryza sativa , Citrus sp. , and Glycine max by only one locus [ 32 ], two in apple [ 33 ] and three in tomato [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid growth rate of S. polyrhiza requires sufficient nutrients, including nitrogen and phosphorus, to maintain its development and normal life cycle. Many S. polyrhiza protein families have been identified such as the lipoxygenase gene family ( Upadhyay et al, 2020 ), WRKY gene family ( Zhao et al, 2021 ), and polyamine biosynthesis pathway ( Upadhyay et al, 2021 ). NRT proteins act as transporters that acquire nitrogen from the environment.…”
Section: Discussionmentioning
confidence: 99%